THE EFFECTS OF AEROBIC CAPACITY, MUSCULAR ENDURANCE, AND BMI ON YOUNG PUPILS’ LEARNING - Singh, Satpal; Singh, Kanwaljeet (International Journal of Psychosocial Rehabilitation, 2021)
Physical fitness and body mass index categories (OB, OW, NW, and UW) in prepubertal children were the primary goals of this study. The anthropometric and physical fitness parameters of 30472 Italian kids (6–11 years old) were gathered from a convenience sample. Léger, agility shuttle, long jump, and frontal toss of the basketball, Sit & Reach, and standing balance were all employed in the field-based testing In addition, the frontal throw test scores of UW and NW females in older children become increasingly disparate from those of younger children. According to our findings, the influence of body mass index on children’s physical fitness increases as they become older. Cardiovascular fitness is significantly impacted by OW/OB but agility and lower-limb strength are favourably affected. Upper limb power is reduced by UW. Preventing childhood obesity, obsessive-compulsive disorder, and underweight (UW) in early life is critical to a child’s health and fitness development.